2010
DOI: 10.1124/jpet.110.174219
|View full text |Cite
|
Sign up to set email alerts
|

Bis-Halogen-Anthraniloyl-Substituted Nucleoside 5′-Triphosphates as Potent and Selective Inhibitors ofBordetella pertussisAdenylyl Cyclase Toxin

Abstract: Whooping cough is caused by Bordetella pertussis and still constitutes one of the top five causes of death in young children, particularly in developing countries. The calmodulin-activated adenylyl cyclase (AC) toxin CyaA substantially contributes to disease development. Thus, potent and selective CyaA inhibitors would be valuable drugs for the treatment of whooping cough. However, it has been difficult to obtain potent CyaA inhibitors with selectivity relative to mammalian ACs. Selectivity is important for re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0

Year Published

2011
2011
2018
2018

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 32 publications
0
22
0
Order By: Relevance
“…MANT-nucleotides and the structurally related TNP-nucleotides inhibit ACs 1, 5 and 6 with similar potencies, whereas AC2 is inhibited only ∼10-fold less potently [22,26-29]. Hence, as for the classic P-site inhibitors, no compelling isoform-specificity was observed [15].…”
Section: Exploring the Catalytic Site Of Macs With Mant- And Tnp-nuclmentioning
confidence: 99%
“…MANT-nucleotides and the structurally related TNP-nucleotides inhibit ACs 1, 5 and 6 with similar potencies, whereas AC2 is inhibited only ∼10-fold less potently [22,26-29]. Hence, as for the classic P-site inhibitors, no compelling isoform-specificity was observed [15].…”
Section: Exploring the Catalytic Site Of Macs With Mant- And Tnp-nuclmentioning
confidence: 99%
“…CaCl 2 , MnCl 2 tetrahydrate and MgCl 2 hexahydrate (highest quality) were purchased from Merck (Darmstadt, Germany). Mono-and bis-(M)ANT nucleotides were synthesised as described (Taha et al 2009;Geduhn et al 2011).…”
Section: Methodsmentioning
confidence: 99%
“…Despite these reservations regarding MANT-ITP, the long-term goal of obtaining isoform-specific AC inhibitors is not elusive. Specifically, we have shown that certain bis-MANT-substituted nucleotides are very potent inhibitors of the Bordetella pertussis AC toxin CyaA (Geduhn et al, 2011), with high selectivity relative to mammalian ACs. The identification of Bis-MANT nucleotides as potent and selective CyaA inhibitors resulted from a relatively small medicinal chemistry program and not from an extensive high-throughput screening effort.…”
Section: Discussionmentioning
confidence: 99%
“…Specifically, upon binding to the substrate-binding site, nonfluorescent inhibitors would quench the large basal or FS-stimulated direct fluorescence or FRET signals. This assay is even feasible to obtain information on relative inhibitor affinity through the analysis of cumulative concentration/quench curves in a single cuvette (Geduhn et al, 2011). Fluorescence assays with MANT-ITP could also be useful to identify allosteric AC inhibitors.…”
Section: Discussionmentioning
confidence: 99%